2012
DOI: 10.1016/j.neuroimage.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between BOLD amplitude and pattern classification of orientation-selective activity in the human visual cortex

Abstract: Orientation-selective responses can be decoded from fMRI activity patterns in the human visual cortex, using multivariate pattern analysis (MVPA). To what extent do these feature-selective activity patterns depend on the strength and quality of the sensory input, and might the reliability of these activity patterns be predicted by the gross amplitude of the stimulus-driven BOLD response? Observers viewed oriented gratings that varied in luminance contrast (4, 20 or 100%) or spatial frequency (0.25, 1.0 or 4.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 65 publications
7
30
0
Order By: Relevance
“…To examine this question, we specifically focused on within-subject changes across load (see Methods), because there may be sources of error that affect between-subject classification performance that are unrelated to differences in behavior (e.g., differences in encoding strategies, Linke et al, 2011b; Vicente-Grabovetsky et al, 2012, or individual differences in signal-to-noise ratio of BOLD signal, Tong et al, 2012). This analysis revealed that, across loads, the observed decrease in peak classifier sensitivity is significantly correlated with an individual’s change in mnemonic precision, r = .58, p = .006.…”
Section: Resultsmentioning
confidence: 99%
“…To examine this question, we specifically focused on within-subject changes across load (see Methods), because there may be sources of error that affect between-subject classification performance that are unrelated to differences in behavior (e.g., differences in encoding strategies, Linke et al, 2011b; Vicente-Grabovetsky et al, 2012, or individual differences in signal-to-noise ratio of BOLD signal, Tong et al, 2012). This analysis revealed that, across loads, the observed decrease in peak classifier sensitivity is significantly correlated with an individual’s change in mnemonic precision, r = .58, p = .006.…”
Section: Resultsmentioning
confidence: 99%
“…For contexts in which there are voxel-level interactions with experimental variables (e.g., some voxels in an ROI do not activate), as would likely occur in many ROIs, increasing the between-subject variability in mean activation may also increase voxel-level variability and the between-subject variability of the voxel-level variances (the τ matrix). Thus, in cases of voxel-by-condition interactions, group-level MVPA may be affected by between-subject variability in activation (see e.g., LaRocque et al 2013; Smith et al 2011; Tong et al 2012). Because of the infinite ways that voxel-by-condition interactions can manifest, it is not possible to give precise a priori predictions for how they impact MVPA in all contexts.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that differences in orientation decodability resulted from differences in the signal-to-noise ratio of V1 responses across stimulus types (Tong et al, 2012). To test for this possibility, we compared the average % signal change in V1 across all stimulus types.…”
Section: Resultsmentioning
confidence: 99%